EXPLORING THE RELATIONSHIP BETWEEN NURSE EMPOWERMENT AND PATIENT SAFETY CULTURE IN HEALTHCARE FACILITIES ACROSS KSA - Jawaza Debiyan Gh Alshammari, Munirah Saleh Dughayyim Alzabni, Radhyah Ali Kassab Alanazi, Nuwayyir Sameer Sayfa Alshammari, Anwar Ibrahim Alshammari, Khznah Ameq M Alanazi, Marihah S M Alharbi, (Chelonian Research Foundation, 2022)
Nurse empowerment and patient safety culture are crucial factors in ensuring high-quality healthcare and optimal patient outcomes. This study aims to explore the relationship between nurse empowerment and patient safety culture in healthcare facilities across the Kingdom of Saudi Arabia (KSA). A cross-sectional survey was conducted among 500 nurses working in various healthcare settings, including public and private hospitals, primary healthcare centers, and specialized clinics. The survey assessed nurses' perceptions of empowerment using the Conditions of Work Effectiveness Questionnaire-II (CWEQ-II) and patient safety culture using the Hospital Survey on Patient Safety Culture (HSOPSC). Descriptive statistics, correlation analysis, and multiple linear regression were used to analyze the data. The findings revealed a significant positive relationship between nurse empowerment and patient safety culture, with structural empowerment and psychological empowerment being the strongest predictors of a positive patient safety culture. The study highlights the importance of fostering nurse empowerment to enhance patient safety culture in healthcare facilities across KSA.